2023
DOI: 10.3346/jkms.2023.38.e39
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation, Depression, and Insomnia in Parent Survivors of Suicide: Based on Korean Psychological Autopsy of Adolescent Suicides

Abstract: Background This study aims to evaluate suicidal ideation, depression, and insomnia among parent survivors of adolescents who died by suicide and their relevant risk factors using psychological autopsy results from South Korea. Methods The participants were 42 parent survivors (10 fathers and 32 mothers) of 35 adolescents who died by suicide. We used the Patient Health Questionnaire-9 and the Korean version of the Insomnia Severity Index to evaluate the mental health of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In our previous study [ 119 ], many adolescents (74.3%) experienced family related trauma, with parental divorce or parent-child separation being the most common (54.3%). In this study, the parents reported that 40% of the deceased experienced family discord during their developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [ 119 ], many adolescents (74.3%) experienced family related trauma, with parental divorce or parent-child separation being the most common (54.3%). In this study, the parents reported that 40% of the deceased experienced family discord during their developmental stage.…”
Section: Discussionmentioning
confidence: 99%